Serologic Response of 2 Versus 3 Doses and Intradermal Versus Intramuscular Administration of a Licensed Rabies Vaccine for Preexposure Prophylaxis. (6th December 2019) - Endy, Timothy P; Keiser, Paul B; Wang, Dongliang; Jarman, Richard G; Cibula, Don; Fang, Hengsheng; Ware, Lisa; Abbott, Mark; Thomas, Stephen J; Polhemus, Mark E
Abstract: Background: The World Health Organization recommends intradermal (ID) administration of rabies vaccine for preexposure prophylaxis. Methods: In a randomized trial in adults assigned to 1 of 6 treatment groups (ID vs intramuscular [IM], 2 vs 3 doses, and controls), rabies neutralizing antibody titers were measured to 1 year postvaccination. Results: ID vaccination produced acceptable antibody levels in all subjects (2- and 3-dose groups). At day 365, acceptable levels were 40% for IM and 50% for ID 2-dose schedule, and 70% for IM and 60% for ID 3-dose schedule. Conclusions: ID rabies vaccination induces acceptable antibody titers at a fraction of the dose. Clinical Trials Registration: NCT02374814.